2011
DOI: 10.1002/jcop.20477
|View full text |Cite
|
Sign up to set email alerts
|

Examining protective factors and risk factors in urban and rural head start Preschoolers

Abstract: This study examined a comprehensive screening model within children attending Head Start programs from urban (n =232) and rural (n = 231) communities. The Devereux Early Childhood Assessment (DECA; LeBuffe & Naglieri, 1999) was used to measure social‐emotional protective factors (i.e., Total Protective Factors [TPF]) and risk factors (i.e., Behavior Concerns [BC]) within children that resided in two different community settings. Children from low‐income rural programs received higher scores on a subscale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The preschool children from rural and urban Head Start Programmes showed lower performance than the normative sample on vocabulary Early Child Development and Care knowledge and emergent literacy skills measured with the PPVT-III and the TERA-3, which was consistent with past research (Aikens et al, 2013;Bracken & Fischel, 2008;Fish & Pinkerman, 2003;Hulsey et al, 2011;Moiduddin et al, 2012). Although it has been noted that the learning context is important in literacy development (Bender et al, 2011;Fish & Pinkerman, 2003;O'Brien et al, 2002), the results of this study did not show a significant difference between the two groups with the exception of the rural children scoring lower on the TERA-3 alphabet subtest.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The preschool children from rural and urban Head Start Programmes showed lower performance than the normative sample on vocabulary Early Child Development and Care knowledge and emergent literacy skills measured with the PPVT-III and the TERA-3, which was consistent with past research (Aikens et al, 2013;Bracken & Fischel, 2008;Fish & Pinkerman, 2003;Hulsey et al, 2011;Moiduddin et al, 2012). Although it has been noted that the learning context is important in literacy development (Bender et al, 2011;Fish & Pinkerman, 2003;O'Brien et al, 2002), the results of this study did not show a significant difference between the two groups with the exception of the rural children scoring lower on the TERA-3 alphabet subtest.…”
Section: Discussionsupporting
confidence: 84%
“…Low maternal education and income have been shown to relate to children's vocabulary and emergent literacy development (Brooks-Gunn & Markman, 2005;Hammer, Farkas, & Maczuga, 2010), and the availability of more adults to read to children could potentially affect home learning and early language skills. Likewise, Bender, Fedor, and Carlson (2011) compared children from rural and urban backgrounds and discovered differences in environmental demands and opportunities. These differences may be related to children's emergent literacy skills.…”
Section: Socioeconomic Statusmentioning
confidence: 98%
“…These differences suggest that this instrument is sensitive to capture existing differences in teachers' perceptions, which are consistent with previous research. For example, the fact that rural teachers perceived themselves has having less teaching social and emotional needs than urban teachers may be understood by the fact that students from rural and urban schools present different tendencies of behaviors problems (S. L. Bender, Fedor, & Carlson, 2011). Students from rural schools present more internalizing problems and students from urban schools tend to present more externalization problems (e.g., Hope & Bieman, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the ways that community poverty manifests across diverse geographical and sociocultural contexts appears to have important implications for its effects on children and families. The urban poor, for example, tend to report better physical health outcomes but worse psychological functioning than the rural poor, with these relationships differing for individuals from diverse sociodemographic and racial/ethnic backgrounds (Amato & Zuo, 1992; Bendar, Fedor, & Carlson, 2011; Glaeser, 2011; Rutter, 1980). Although the mechanisms underlying urban versus rural poverty’s effects on children are relatively poorly understood, researchers have posited that differential concentrations of particular risk and protective factors like crime and social/educational resources across the urbanicity continuum may be responsible (Amato & Zuo, 1992; Rutter, 1980).…”
Section: Neighborhood Urbanicity and Head Start – Evidence For Contexmentioning
confidence: 99%
“…Recent research has found, for example, that urban Head Start families show higher levels of educational engagement but lower levels of parent-child attachment than rural Head Start families (Bender, Fedor, & Carlson, 2011; Keys, 2014). Similarly, national data from the Early Childhood Longitudinal Study Birth Cohort suggest that the lower pre-academic skills of children living in both rural and highly urban settings upon kindergarten entry may be partially explained by higher levels of family socioeconomic adversity in these settings as compared with those in small urban or suburban ones (Grace et al, 2006; Miller & Votruba-Drzal, 2013).…”
Section: Neighborhood Urbanicity and Head Start – Evidence For Contexmentioning
confidence: 99%